Caffeine, CYP1A2 genotype, and endurance performance in athletes - Guest, N.; Corey, P.; Vescovi, J.; El-Sohemy, A. (Medicine & Science in Sports & Exercise, 2018)
Purpose Many studies have examined the effect of caffeine on exercise performance, but findings have not always been consistent. The objective of this study was to determine whether variation in the CYP1A2 gene, which affects caffeine metabolism, modifies the ergogenic effects of caffeine in a 10-km cycling time trial. Methods Competitive male athletes ( n = 101; age = 25 ± 4 yr) completed the time trial under three conditions: 0, 2, or 4 mg of caffeine per kilogram body mass, using a split-plot randomized, double-blinded, placebo-controlled design. DNA was isolated from saliva and genotyped for the -163A > C polymorphism in the CYP1A2 gene (rs762551). Results Overall, 4 mg/kg caffeine decreased cycling time by 3% (mean ± SEM) versus placebo (17.6 ± 0.1 vs 18.1 ± 0.1 min, P = 0.01). However, a significant ( P <0.0001) caffeine-gene interaction was observed. Among those with the AA genotype, cycling time decreased by 4.8% at 2 mg/kg (17.0 ± 0.3 vs 17.8 ± 0.4 min, P = 0.0005) and by 6.8% at 4 mg/kg (16.6 ± 0.3 vs 17.8 ± 0.4 min, P < 0.0001). In those with the CC genotype, 4 mg/kg increased cycling time by 13.7% versus placebo (20.8 ± 0.8 vs 18.3 ± 0.5 min, P = 0.04). No effects were observed among those with the AC genotype. Conclusion Our findings show that both 2 and 4 mg/kg caffeine improve 10-km cycling time, but only in those with the AA genotype. Caffeine had no effect in those with the AC genotype and diminished performance at 4 mg/kg in those with the CC genotype. CYP1A2 genotype should be considered when deciding whether an athlete should use caffeine for enhancing endurance performance.